IUD Contraceptive Use in Couples of Childbearing Age: A Qualitative Study in Southwest Sumba - Radja, Depsiana Keke; Sir, Amelya B.; Sinaga, Masrida (Universitas Nusa Cendana, 2024)
The family planning program revitalization focuses on increasing Long Term Contraception Method/MKJP use, including IUD contraception. Data stated that IUD use in the work area of Tena Teke Health Center was still low, as it only reached 2.42%. The research aims to examine the use of IUD contraception among couples of childbearing ages. The method was descriptive qualitative with a case-study approach. Informants were determined by using a purposive sampling technique with the criteria of women of childbearing age >35 years old, who had >2 children, and who used/had ever used an IUD. The research results found that informants who were not IUD users felt afraid because they thought IUD had side effects, including abdominal pain and discomfort during sexual intercourse. In contrast, informants who used IUDs believed that the contraceptive was safe to use. Husbands' support for non-IUD users was still limited to accompanying spouses to health facilities but not present during consultation and examination, while IUD informants reported receiving support from their husbands. Informants who did not use an IUD were likely to believe other people's incorrect experiences and stories compared to information from health workers. This was different from IUD informants who obtained clear and correct information about IUDs directly from midwives. Family planning health workers need to increase education by involving husbands in family planning programs.